P435 Rapidity of symptomatic and inflammatory biomarker improvements following upadacitinib induction treatment: data from the U-ACHIEVE study. (25th January 2019) - D'Haens, G; Loftus Jr, E V; Higgins, P D R; Panes, J; Panaccione, R; Zhou, W; Cataldi, F; Lee, W-J; Huang, B; Xie, W; Vermeire, S
Abstract: Background: Upadacitinib (UPA), an oral, selective Janus Kinase 1 inhibitor, demonstrated improved efficacy compared with placebo (PBO) in a Phase 2b induction study in patients with moderately-to-severely active ulcerative colitis (UC). 1 This analysis assessed the time to onset of symptomatic improvement, clinical response, and improvement in biomarkers during the induction phase of U-ACHIEVE. Methods: Adult patients with moderately to severely active UC were randomised to double-blind therapy with extended-release UPA 7.5, 15, 30, 45 mg once daily (QD) or PBO for 8 weeks. Data from patient daily diary (as observed) on Mayo stool frequency subscore (SFS, 0–3) and rectal bleeding subscore (RBS, 0–3), as well as bowel urgency (BU, Y/N) and abdominal pain (AP, 0–3) were examined daily in the first 15 days of therapy. The proportion of patients with clinical response per partial Mayo score (decrease from baseline [BL] in Partial Mayo score ≥ 2 points and ≥ 30%, PLUS a decrease in RBS ≥ 1 or an absolute RBS ≤ 1), and the change from BL in high-sensitivity C-reactive protein (hs-CRP) and faecal calprotectin (FC) were evaluated at Week 2. Comparisons between each UPA dose with PBO for proportions was assessed by Cochran–Mantel–Haenszel tests and mean change from BL by analysis of covariance with treatment and randomisation factors as covariate. Results: A total of 250 patients were randomised. The mean SFS was 2.7 and RBS was 1.7 at BL. Trends of higher proportion of patients achieving symptom improvement in SFS and RBS were observed in the UPA 45 mg group than PBO as early as Day 4 (figure) and reached statistical significance ( p < 0.05) by Day 8 in SFS, RBS, BU, and AP (Table 1). At Week 2, the proportion of patients with clinical response and the median change from BL in hs-CRP was statistically significantly greater in the UPA 15, 30, and 45 mg QD groups vs. the PBO group (Table 2). Conclusions: Early symptomatic improvement, as early as Day 4, was observed with UPA treatment in patients with active UC, concurrent with a rapid decrease in markers of inflammation. Reference 1. Sandborn WJ, Ghosh S, Pans J, et al . Efficacy and safety of upadacitinib as an induction therapy for patients with moderately-to-severely active ulcerative colitis: data from the phase 2b study U-ACHIEVE. In: United European Gastroenterology (UEG) Week, Presentation #OP195, 20–24 October 2018, Austria Center Vienna, Vienna, Austria.